Getting in (and out of) the loop: regulating higher order telomere structures - Luke-Glaser, Sarah; Poschke, Heiko; Luke, Brian (Frontiers in oncology, 2012)
The DNA at the ends of linear chromosomes (the telomere) folds back onto itself and forms an intramolecular lariat-like structure. Although the telomere loop has been implicated in the protection of chromosome ends from nuclease-mediated resection and unscheduled DNA repair activities, it potentially poses an obstacle to the DNA replication machinery during S phase. Therefore, the coordinated regulation of telomere loop formation, maintenance and resolution is required in order to establish a balance between protecting the chromosome ends and promoting their duplication prior to cell division. Until recently, the only factor know to influence telomere looping in human cells was TRF2, a component of the shelterin complex. Recent work in yeast and mouse cells has uncovered additional regulatory factors that affect the loop structure at telomeres. In the following “perspective” we will outline what is known about telomere looping and highlight the latest results regarding the regulation of this chromosome end structure. We will speculate about how the manipulation of the telomere loop may have therapeutic implications in terms of diseases associated with telomere dysfunction and uncontrolled proliferation.